A 2D WLP‐FDTD method with low numerical dispersion using artificial anisotropy parameters. Issue 1 (10th January 2021) - Ma, Ping; Chen, Wei‐Jun; Tian, Jing; Shi, An‐Hua; Zhang, Ning
Abstract: A finite‐difference time‐domain method is proposed to reduce the numerical dispersion error induced by the non‐uniform meshing of multiscale configurations utilizing weighted Laguerre polynomials. The update functions of two‐dimensional TE z waves are obtained with the introduction of the artificial anisotropic parameters in the derivation procedure. The theoretical analysis of utilizing artificial anisotropic weighted Laguerre polynomial finite‐difference time‐domain for the suppression of numerical dispersion error is also presented. To verify the validation of the proposed method, the propagation of plane waves in a two‐dimensional cavity filled with the dielectric material is modelled. Compared with the existing approaches, the proposed method achieves low numerical dispersion error and improved accuracy without increasing computational cost.